The Effectiveness of a Project-Based Learning Based Teaching Module on the Area of Squares and Rectangles: A Trial Study in Fourth Grade Elementary Classrooms - Gevina Miftah Hulzannah Hasibuan; Syafri Ahmad; Salmaini Salmaini (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
This study aims to analyze the effectiveness of a mathematics teaching module on the topic of the area of squares and rectangles implemented for fourth-grade elementary school students through the Project-Based Learning (PjBL) model. The background of the study stems from students’ low conceptual understanding of area, which is still focused on memorizing formulas, and their weak understanding of units of area. The method used is descriptive qualitative, involving observation of the learning process, analysis of students’ worksheets (LKPD), and identification of obstacles encountered during the trial implementation. The results show that the teaching module helps students understand the concept of area concretely through the use of grids and the measurement of real objects. Students demonstrated high engagement in group work, discussions, and project result presentations. The challenges encountered include difficulty distinguishing between area and perimeter, lack of accuracy in counting unit squares, and weak understanding of square units. Overall, the teaching module is considered effective in improving conceptual understanding, learning motivation, and student engagement, although it still requires reinforcement of visual instructions and strategies for calculation efficiency.